RIDGE SOWING IMPROVES ROOT SYSTEM, PHOSPHORUS UPTAKE, GROWTH AND YIELD OF MAIZE (Zea mays L.) HYBRIDS - M. B. Khan; R. Rafiq; M. Hussain; M. Farooq; K. Jabran (Journal of Animal and Plant Sciences, 2012)
Adequate and balanced supply of essential nutrients, promising cultivars and improved planting methods are prime important to realize the maximum potential of different maize hybrids. This study was conducted to evaluate the response of different planting methods on rooting system, crop growth, phosphorus (P) uptake and yield of different maize (Zea mays L.) hybrids. Three maize hybrids viz. 6621 (H1), 919 (H2) and KS-64 (H3) were planted in flat sowing (P1 = 75 cm spaced rows), ridge sowing (P2 = 75 cm spaced ridges) and bed sowing (P3 = 120‑30 cm apart beds). Better root growth, P uptake, agronomic and yield related traits were observed in ridge sowing followed by bed sowing; although there was non-significant effect of sowing methods on plant population, cob length and harvest index. Amongst the hybrids tested, hybrid 919 showed better performance for most of the parameters studied; although there was no difference among the hybrids for plant population, plant height, number of rows per cob and harvest index. Interactive effect of planting methods and different maize hybrids was also significant for most of the traits studied except plant population, number of rows per cob and harvest index. Maize hybrid 919 when sown on ridges showed maximum root and crop growth, P uptake and yield than rest of the combinations. Strong correlation of lateral roots was observed with grain size, grain yield and grain P contents. To conclude, root growth better ensured the P uptake and use efficiency which resulted in better crop growth and yield while maize hybrid 919 grown on ridges efficiently utilized P and exhibited higher grain yield.
Keywords: Ridge sowing; maize hybrids; P uptake; root growth rate; growth; grain yield.